О жанровом своеобразии „Современной идиллии” Михаила Салтыкова-Щедрина - Mark Sokolanskij (Studia Rossica Posnaniensia)
The article focuses on the genre of Russian satirist Mikhail Saltykov-Shchedrin’s book The Modern Idyll. Special attention is paid to the traditions of a cervantesian type of novel in the book, the ironic code in the title and narration, real objects of bitter political satire, a great number of literary quotations, reminiscences and so on. On the whole the novel may be qualified as a novel-pamphlet.